Development of dissolving microneedles for delivery of cancer cells membrane antigens - Lobita, Maria Margarida Dias Carmona (2021)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia.